It Is? It Is Not? Identifying Portulaca by Morphology and DNA Barcodes - Fam, Jia Yee; Yu, Hai Ping; Fathimath, Sumeyha; Selvarajah, Geeta (European Publisher, 2019)
Amongst Portulaca species are weeds but also medicinal herbs and ornamentals. Differentiation between weeds and crops enable early removal of weeds preventing retardation of crop growth. Authenticating medicinal herbs prevents the sale of substitutions that lowers the effectiveness of the medicine, and potentially endangers lives. Species identification thus helps attain Sustainable Development Goals 2, 3, 14, and 15 of the United Nations. Identification using DNA barcoding is recommended, but barcoding may fail depending on plant groups, sampling regions, loci and data analysis methods used. Thus, BLAST and tree topology was used to test DNA markers of nuclear loci (ITS1 and ITS2) and chloroplast loci (rbcl and trnL-F) for their ability to identify or differentiate Malaysian plant species morphologically characterised as Portulaca oleracea, Portulaca umbraticola, and Portulaca grandiflora. The locus ITS1 enabled the identification of two of the species correctly using standard BLAST scores and discriminated all three species using tree topology. ITS2 could identify all three species accurately but only using a BLAST, based on secondary structure alignment. The rbcl locus was unable to identify or discriminate the species due to lack of variability between sequences of different species. While trnL-F could not identify using BLAST because the database is currently not populated with sequences for all species, resulting in identification to the most closely related species with sequences on the database, which was incorrect. Thus, we recommend the use of ITS1 and ITS2 loci for identifying Portulaca species until trnL-F sequences of more species populate the database for dependable species identification.